The nature of strong chalcogen bonds involving chalcogen-containing heterocycles - Haberhauer, Gebhard; Gleiter, Rolf (Angewandte Chemie. International edition, 2020)
Chalcogen bonds are σ hole interactions and have been used in recent years as an alternative to hydrogen bonds. In general, the electrostatic potential at the chalcogen atom and orbital delocalization effects are made responsible for the orientation of the chalcogen bond. Here, we were able to show by means of SAPT calculations that neither the induction (orbital delocalization effects) nor the electrostatic term is causing the spatial orientation of strong chalcogen bonds in tellurium-containing aromatics. Instead, steric interactions (Pauli repulsion) are responsible for the orientation. Against chemical intuition the dispersion energies of the examined tellurium-containing aromatics are far less important for the net attractive forces compared to the energies in the corresponding sulfur and selenium compounds. Our results underline the importance of often overlooked steric interactions (Pauli repulsion) in conformational control of σ hole interactions.
Gesehen am 28.10.2025